OPTIMIZING MOBILE APP PERFORMANCE THROUGH ADAPTIVE RESOURCE MANAGEMENT - Michael Gevorgyan (Modern American Journals, 2025)
The article discusses methods of adaptive resource management of mobile applications, including dynamic distribution of processor time, memory and network resources. An analysis of existing approaches is conducted, an architecture of an adaptive resource manager is proposed that provides a balance between performance and energy consumption. The experimental results show that the implementation of adaptive algorithms allows reducing the response time of applications by 15-25% and reducing memory consumption by 10-18%.
Keywords: Mobile applications, performance optimization, adaptive resource management, energy consumption, dynamic allocation.